La inclusión del tiempo en la estructura espacial de Jorge E. Eielson y su expresión plástica a través de la intervención en materiales textiles - Rodríguez Canales, María Milagros (2020)
The following article, analyzes the existence of a spatial structure within the work of Jorge Eduardo Eielson. This system is thought to be based upon the author’s perception of time as a constituent part of the space phenomenon and developed consequently in his plastic work through the shaping of textile materials. Thus, exploring Eielson’s space will include the abstract notions established by the author in essays, interviews and non objetual works, as well as their transition into shapes that are definite and material embodied through the use of fabrics.